Foreign experiences in improving the implementation of tax obligations (Eurasian Research Bulletin, 2023)
In this article, refers to a topic that explores the challenges of improving the execution of tax obligations by taxpayers. The study delves into the various factors that contribute to non-compliance, such as the complexity of tax laws, lack of taxpayer education, inadequate tax administration, and corruption. Additionally, the study reviews various measures that can be taken to address these challenges and promote tax compliance, such as simplifying tax laws, increasing taxpayer education and awareness, improving tax administration, and strengthening anti-corruption measures. The research draws from a wide range of literature, including academic articles, government reports, and policy papers, to provide a comprehensive analysis of the issues related to improving tax compliance